2015
DOI: 10.3758/s13414-014-0824-y
|View full text |Cite|
|
Sign up to set email alerts
|

A robust asymmetry in loudness between rising- and falling-intensity tones

Abstract: Tones rising in intensity over a few seconds are perceived as louder than symmetrical tones falling in intensity. However, the causes for such perceptual asymmetry, as well as its magnitude and dependency on contextual and methodological factors remain unclear. In this paper, two psychophysical experiments were conducted to measure the magnitude of this asymmetry for 2-s, 15-dB intensity-varying tones in different conditions. In the first experiment, participants assessed the global loudness of rising-and fall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 59 publications
2
10
0
Order By: Relevance
“…The predicted asymmetry was1.3 dB for WN, 2.1 dB for MT,1 .5 dB for RWNa nd PT.T he observed asymmetry wasq uite well explained by the model for the sound that does not elicit pitch (WN) whereas it wasunderestimated for the sounds that elicit pitch (RWN and PT). ForMT, the loudness model slightly overestimated the asymmetry.Our results are in agreement with those of Ries et al [3] who found that LTLpredicted well the loudness asymmetry for white noise of 500 ms, and with those of Ponsot et al [6], who predicted an asymmetry of 1.24 dB for a1-kHz pure tone of 2sv arying between 55 and 70 dB, using the LTL model.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The predicted asymmetry was1.3 dB for WN, 2.1 dB for MT,1 .5 dB for RWNa nd PT.T he observed asymmetry wasq uite well explained by the model for the sound that does not elicit pitch (WN) whereas it wasunderestimated for the sounds that elicit pitch (RWN and PT). ForMT, the loudness model slightly overestimated the asymmetry.Our results are in agreement with those of Ries et al [3] who found that LTLpredicted well the loudness asymmetry for white noise of 500 ms, and with those of Ponsot et al [6], who predicted an asymmetry of 1.24 dB for a1-kHz pure tone of 2sv arying between 55 and 70 dB, using the LTL model.…”
Section: Discussionsupporting
confidence: 93%
“…Their global loudness (that is, the overall loudness of the sound overits entire duration)isalso greater than the global loudness of afalling sound. At the point of subjective equality (PSE), a falling 1-kHz pure tone varying over15-dB has arms level that is 4dBhigher than that of its symmetrical rising version [6] .This global loudness difference is usually called loudness asymmetry.V arious studies have attempted to explain and model the global loudness asymmetry [7,6]. Ponsot et al [7] showed alarger loudness asymmetry for pure tones than for broadband noises.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous psychophysical experiments have shown that sounds whose intensity is ramping up with time (up-ramps) are globally perceived as louder or changing more in loudness than their time-symmetric opposites (down-ramps). This perceptual asymmetry has been observed for a wide range of sound durations 10 11 12 13 and is proposed to emphasize approaching sound sources relative to sources moving away 10 to favour threat detection. The physiological bases of this perceptual asymmetry are yet unknown, but several studies found the activity correlates in later stages of the auditory system.…”
mentioning
confidence: 88%
“…Specifically, global loudness significantly increased in magnitude as the region of each up-ramp increased from 45-60 dB SPLt o 75-90 dB SPLfor 15 dB ranges, and 45-75 dB SPL to 60-90 dB SPLfor 30 dB ranges. This result is not surprising, as aglobal loudness impression in response to an up-ramp is expected to increase as the ramp'saverage intensity,region of change, and end-levelincreases [6,23,31]. However,w hen as eparate group of participants rated global loudness change, very similar results were observed to the group that rated global loudness.…”
Section: Discussionmentioning
confidence: 63%